Si-atoms substitutions effects on the electronic and optical properties of coronene and ovalene. (6th November 2018) - Mocci, P; Cardia, R; Cappellini, G
Abstract: We report a computational comparative study of the ground and excited states properties of graphene nanoribbons, analyzing the case of coronene (C24 H12 ) and ovalene (C32 H14 ) and their silicon-atoms substituted counterparts with single, double and triple atomic insertions. We used density functional theory (DFT) and time-dependent DFT to quantify the effects on the electronic and optical properties as a result of the chemical modifications. In particular, we compared ground-state total energies, electron affinities, ionization energies, fundamental gaps and optical absorption spectra, between the original systems and each substituted one. For both the molecules, we observed a general reduction of the fundamental gap after chemical modification. Concerning the optical properties, therefore, we observed a redshift of the optical onset in all the cases; in particular, we have found that, in one ovalene and coronene trimer-substituted configuration, the absorption edge takes place in the IR.